Novos compostos de paládio e rutênio com atividade antitumoral - Serrano, Fabiana do Amaral [UNIFESP] (2009)
Melanoma is the most aggressive form of skin cancer mainly because of the high degree of tumor cell proliferation, invasion and metastasis. Less than 10% of metastatic melanoma patients show 5 years survival. Single drug chemotherapy is well tolerated but associated with low response rates. Associations of chemotherapeutic agents approved for human use are related to low response rates, without improvement on side effects. Therefore, the identification of new antitumor agents is critical to melanoma treatment, and this study aimed to evaluate the antitumor effect of novel palladium and rutheniun derived chemotherapeutic drugs in the preclinical model of murine melanoma B16F10-Nex2. A cyclopalladated compound, [Pd2(S(-)C2, N-dmpa)2 (μ-dppe)Cl2], named C7A was previously evaluated by our group. The complex showed high antitumor and low toxicity in vivo, however, the targets for this compound in tumor cells were not determined yet. In this work we demonstrated that C7A interacts with thiol proteins present in the mitochondrial membrane, leading to an abrupt reduction of extracellular acidification, collapse of mitochondrial membrane potential and Bax translocation to the interior of this organelle. It was also observed an increase in intracellular calcium concentrations, originated from cellular organelles as well as from extracellular medium. These initial effects caused activation of effector caspases, nuclear condensation, DNA degradation and dramatic morphological changes in these cells. All these data suggests that the cyclopalladated 7A induces the intrinsic pathway apoptotic cell death on B16F10-Nex2 murine melanoma cells. Human tumor cells are sensitive to this compound and mitochondria also seem to be the target for C7A on these cells. Cyclopalladated 7A significantly reduced the number of pulmonary nodules with no apparent toxicity, indicating that this compound is also active against metastatic melanoma lesions. Antitumor activity of several nitrosyl tetraammine ruthenium compounds with general formula (trans-[RuII(NH3)4(L)NO+], where L corresponds to different stabilization ligands, were evaluated. These compounds are nitric oxide (NO) donors in biological media. All tested compounds were cytotoxic in vitro to human and murine tumor cells. Some compounds were selected and evaluated in vivo, showing numerous side effects in association with the antitumor effect. However, it was found that the compounds where the NO was replaced by a sulfate group, used regularly as a negative control for NO-donor ruthenium complexes, showed a pronounced antitumor activity and low toxicity in vivo, delaying subcutaneous tumor development and extending survival of treated animals. Sulfate compounds also reduced the number of metastatic lung nodules with no apparent toxicity. These compounds were also cytotoxic for human tumor cells in vitro, and the morphological alterations, phosphatidylserine externalization, nuclear condensation and DNA degradation observed after cell treatment suggested that sulfate tetraamine compounds induced an apoptotic cell death. Both evaluated chemotherapeutic drugs open new possibilities for malignant melanoma treatment.